Материалы к фауне и экологии трубковертов (Coleoptera, Attelabidae) Украины. Сообщение I - Лаврух, О.В. (Вестник зоологии, 1971)
In the territory of 16 regions of the Ukraine 22 species of leaf rolles were observed
from the genera Auletobius Des b r., Laciorhynchites J e k., Pselaphorhynchites
S с h i l s., Coenorrhinus Thorns. , Homalorhynchites V о s s., Haplorhyrichites V о s s.,
Involoulus S c h r a n k., Rhynchites S с h n e i d.
The faunistic composition data on ecological peculiarities distribution and economic
value of the above-mentioned species of leaf-rollers are given.